2022
DOI: 10.1155/2022/7607993
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Uptake of Antenatal Tetanus Toxoids Containing Vaccine by First-Time Mothers in Nigeria: Findings from the 2018 Nigerian Demographic Health Survey

Abstract: Background. Maternal and neonatal tetanus remains a public health problem in low-and-middle-income countries despite the increasing investment in tetanus toxoid containing vaccines (TTCV). Nigeria still records fatalities from tetanus, predominantly in women of reproductive age and in newborns. This is largely due to poor access to vaccinations and high rates of unsupervised labour and childbirth. We aim to investigate the antenatal uptake of TTCV and associated factors among first-time pregnant women in Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
0
1
1
Order By: Relevance
“… 2 However, the result contradicts the findings of a multicountry study 16 that found that adults were more likely to be protected against tetanus than adolescent girls. Also, the finding contrasts with a related study from Nigeria 17 that found no significant association between age and the likelihood of being protected against tetanus. A plausible explanation for this association could be that health education on vaccination against tetanus often targets adolescent girls and young women due to their likelihood of engaging in risky behaviours such as unprotected sex and having multiple sexual partners.…”
Section: Discussioncontrasting
confidence: 99%
“… 2 However, the result contradicts the findings of a multicountry study 16 that found that adults were more likely to be protected against tetanus than adolescent girls. Also, the finding contrasts with a related study from Nigeria 17 that found no significant association between age and the likelihood of being protected against tetanus. A plausible explanation for this association could be that health education on vaccination against tetanus often targets adolescent girls and young women due to their likelihood of engaging in risky behaviours such as unprotected sex and having multiple sexual partners.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding corroborates with previous studies that found higher likelihood of tetanus toxoid vaccination uptake among women who were employed or working [17,40,41]. The financial earnings of working women could have empowered them with the purchasing power to afford transportation to the facility and cost of health services in situations where the services were not entirely free or not covered by health insurance [26,40,[42][43][44][45].…”
Section: Discussionsupporting
confidence: 90%
“…Masih rendahnya angka cakupan IMD dalam penelitian ini dibandingkan angka cakupan provinsi dan nasional perlu mendapatkan perhatian karena keberhasilan IMD menjadi faktor penting keberhasilan dan keberlangsungan praktik ASI Eksklusif. 18,19 Selain itu IMD juga penting untuk mencegah mortalitas dan morbiditas bayi baru lahir karena dalam kolostrum yang dikonsumsi bayi saat Determinan Inisiasi Menyusui Dini Pada Ibu Postpartum Di Kota Tangerang (Apriningsih, dkk) IMD banyak mengandung protein whey dan mineral,dan probiotik yang sangat bermanfaat untuk imunitas bayi. 20 Ibu post partum yang berhasil melakukan IMD juga terhindar dari risiko menderita depresi post partum.…”
Section: Pembahasanunclassified